Connotative and Denotative Meanings of Justin Bieber’s Song Lyrics Ghost and Hold on in the Album Justice - Tiara Putri Setyaningsih; Didit Kurniadi; Indah Arvianti (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
A lyrical analysis of Justin Bieber’s album reveals how emotional interpretation and literal meaning are intricately intertwined. Words such as ’I miss you more than life’ in particular convey a deep emotional bond that can be connoted with feelings that go beyond words, relating to memories and loss that are relevant to the listener’s experience. With an emphasis on the use of denotative and connotative meanings and the use of qualitative methods, this research examines how connotations and denotations are used in the lyrics of Justin Bieber’s song. After analyzing the data collected from the song lyrics, this study identified three positive, two neutral, and one negative connotation types. Additionally, emotional power in song lyrics conveys difficult concepts such as love, regret, and self-determination that can be found in the lyrics. This method makes music an effective medium to convey emotional experiences.